Lewy body cortical involvement may not always predict dementia in Parkinson's disease. Issue 7 (1st July 2003) - Colosimo, C; Hughes, A J; Kilford, L; Lees, A J
Abstract : Background: The presence of Lewy bodies (LB) in the neocortex and limbic system in patients with Parkinson's disease (PD) is commonly thought to be linked with cognitive impairment. The authors present here a series of patients with diagnosis of PD in life and no significant cognitive impairment who, at necropsy, satisfied the current neuropathological criteria for dementia with Lewy bodies (DLB). Methods: Two hundred and seventy six brains with PD pathology were examined at the Queen Square Brain Bank in London between 1993 and 1999. The neuropathological diagnosis was PD, but 117 patients also had sufficient LB involvement above the brain stem to satisfy the current neuropathological criteria for DLB (50 patients had a neuropathological picture consistent with the limbic category of DLB and 67 with neocortical DLB). Forty eight cases were excluded who developed early cognitive impairment together with motor features of parkinsonism, 12 cases for lack of detailed clinical history, and 19 cases with coexistent features of advanced Alzheimer's disease changes. Thirty eight patients (13.8% of the total with PD pathology and 32.5 % of the total with DLB pathology) were found where there was no or very late cognitive impairment reported in the clinical records. Results: Selected cases were 24 men and 14 women, with a mean (SD) age at onset of parkinsonian symptoms of 60.1 (10.1) years and a mean disease duration of 15.3 (5.5) years. At some time during the evolution of the disease 21 patients developed different degrees of cognitive impairment (after a mean disease duration of 12.2 (4.8) years). Clinical diagnosis at death was PD in 10 cases and PD with dementia in 11. In the remaining 17 patients no history of cognitive impairment was ever recorded in life and all of them had a clinical diagnosis of PD at death; in this subgroup, nine patients later revealed a neuropathological picture consistent with limbic (or transitional) category of DLB and eight with neocortical DLB. Interestingly, in all these patients the parkinsonian features including the response to dopaminergic drugs were indistinguishable from classic brain stem PD. Conclusions: The authors demonstrate that the classic pathology of DLB can commonly be seen outside the generally accepted clinical spectrum for DLB and that important factors other than the absolute number of LB in the neocortex and limbic system influence the development of cognitive impairment in PD. Furthermore, the pathology of PD may be indistinguishable from that reported in DLB, suggesting that the two clinicopathological syndromes may be attributable to the same biological abnormality.